Hubungan Budaya Makan Dan Ekonomi dengan Kejadian Kekurangan Energi kronik (KEK) - Siregar, Nurelilasari; Lola Pebrianthy; Murni Ariani Harefa; ⁠Ita Arbaiyah; Sarli Saragih (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKes Banyuwangi, 2024)
Chronic Energy Deficiency (CED) in pregnant women is influenced by various factors, including economic status and a culture of abstinence from food. This study aims to identify the relationship between economic status and eating culture with CED in the Hutaimbaru Health Center work area in July 2024 using a cross-sectional design with data collection using a questionnaire. Study was using total sampling and got 35 pregnant women, and data analysis was using the Chi-square test. The results showed a relationship between eating culture and CED (p = 0.022) and between economic status and CED (p = 0.011). It was concluded that economics and eating culture are related to the incidence of CED. It is recommended that health workers strengthen health promotion efforts by improving the quality of education and counseling, as well as providing motivation in health services, especially those related to the prevention and treatment of CED in pregnant women.